WIELOJĘZYCZNOŚĆ ZRÓWNOWAŻONA? KRAJOBRAZ JĘZYKOWY POLSKO-CZESKIEGO POGRANICZA W UJĘCIU EKOLINGWISTYCZNYM (PRZYPADEK DUSZNIK ZDROJU I HRONOVA) - STECIĄG, MAGDALENA; KARMOWSKA, ANNA (Slavia Occidentalis, 2020)
The aim of the article is to analyse the linguistic landscape of the Polish-Czech borderland with particular emphasis placed on the number and hierarchy of languages existing in the public space. A static study will be carried out i.e. a study of the language(s) of public road signs, names of streets and squares, public-access buildings, signs on businesses and shops, hoardings etc. The research material comes from two small towns: Duszniki Zdrój in Poland and Hronov in the Czech Republic, both aspiring to become local tourist centres. The global vs. local opposition is of importance to the assumptions made in the study because the language will be regarded as a local practice (Pennycock, 2010). In conclusion, the study will examine the thesis that the local linguistic landscape is a testimony to a transition from a monolingual paradigm towards a “post-monolingual condition” (Yildiz, 2012). It will also be very interesting to find out which configuration of the languages can be considered sustainable in terms of the area’s multilingual nature.